0230 Mild and Acute Sleep Loss Negatively Impacts Vigilance Reflected by Reduced Neural Sensory Processing, Motor Preparation and Execution. (27th April 2018) - Benoit, A; Stojanoski, B; Ray, L; Zandi, A; Quddus, A; Comeau, F; Fogel, S
Abstract: Introduction: The behavioural and cognitive consequences of severe sleep deprivation are well understood. Surprisingly, relatively little is known about the EEG correlates of mild and acute sleep restriction during tasks demanding sustained vigilance for prolonged periods of time during the day. Event-related potential (ERP) paradigms can reveal insight into the neural correlates of sensory processing and behavior that is impaired with reduced alertness as a consequence of sleep loss. Here, we investigated the impact of reduced vigilance following mild sleep restriction (vs. well-rested) to better understand the associated behavioural consequences and changes in information processing revealed by EEG. Methods: Eighteen participants (age 20–26, median=21) were instructed to sleep from 1-6am in the "sleep restricted" (SR) condition, or from 12-9am in the "normal sleep" (NS) condition, verified via actigraphy. Following each night, participants completed 6 sessions of 100 trials of the Psychomotor Vigilance Task (PVT) with simultaneous EEG recording. All testing was completed between 1-3pm (during the circadian trough). Results: More lapses occurred and responses slowed in the SR vs. NS condition (F(1, 17)=8.89, p=0.008; F(1, 17)=4.78, p=0.043). Lapses increased and responses slowed over the course of the 6 sessions (F(5, 85)=10.05, p<0.001; F(5, 85)=4.49, p=0.001). A similar pattern was observed for subjective sleepiness. We compared visually-evoked potentials (VEP) in SR vs. NS and found differences at 316–449 ms, maximal at parietal/occipital cortex. We also investigated electrophysiological signs of motor-related processing by comparing lateralized readiness potentials (LRP), and found reduced LRPs in the fastest responses in the SR vs. NS condition at 70-40ms before, and 115-158ms after a response was made. Conclusion: As expected, vigilance was reduced (e.g., increased lapses, response slowing) following mild and acute SR. Late VEPs were reduced after SR, as was motor-related LRPs for the fastest reaction times. These results suggest that even a single night of mild sleep restriction can negatively impact vigilance, reflected by reduced sensory processing capacity, and dulls motor preparation and execution. Support (If Any): Research support from NSERC Engage and Engage Plus grants to SF and ACS-Corp.